Adsorption characteristics of an enteric virus-binding protein to norovirus, rotavirus and poliovirus - Imai, Takahiro (BioMed Central, 2011)
BACKGROUND: Water contamination with human enteric viruses has posed human health risks all over the world. Reasonable and facile methodologies for recovering and quantifying infectious enteric viruses in environmental samples are needed to address the issues of waterborne viral infectious diseases. In this study, a bacterial protein that has a binding capability with several enteric viruses is discovered, and its binding characteristics were investigated for utilizing it as a viral adsorbent in virus recovery and detection technologies. RESULTS: A gene of an enteric virus-binding protein (EVBP), derived from a monomer of a bacterial chaperon protein GroEL, was successfully acquired from a genomic DNA library of activated sludge microorganisms with nested PCR. Equilibrium dissociation constants between EVBP and norovirus-like particles (NoVLPs) of genotypes GI.7 and GII.4, estimated with quartz crystal microbalance method, were 240 and 210 nM, respectively. These values of equilibrium dissociation constant imply that the binding affinity between EVBP and NoVLPs is 1 to 3-log weaker than that in general antigen-antibody interactions, but about 2-log stronger than that in weak specific interactions of proteins with cations and organic polymers. The adsorptions of EVBP to norovirus, group A rotavirus and poliovirus type 1 were found to be significant in enzyme-linked immunosorbent assay. Meanwhile, the binding of native GroEL tetradecamer to viral particles was weaker than that of EVBP, presumably because of a steric hindrance. The small molecule of EVBP could have an advantage in the access to the surface of viral particles with rugged structure. CONCLUSIONS: EVBP that has a broad binding spectrum to enteric viruses was newly discovered. The broad binding characteristic of EVBP would allow us to utilize it as a novel adsorbent for detecting diverse enteric viruses in clinical and environmental samples.